The ventilatory component of the muscle metaboreflex is overstimulated in transthyretin cardiac amyloidosis patients with poor aerobic capacity - Monfort, Astrid; Thevenet, Eugenie; Enette, Lievyn; Fagour, Cedric; Inamo, Jocelyn; Neviere, Remi (Frontiers in Physiology, 2023)
Background: The exercise pressor reflex, i.e., metabo- and mechano-reflex, partially regulates the control of ventilation and cardiovascular function during exercise. Abnormal exercise pressor reflex response has been associated with exaggerated ventilatory drive, sympathovagal imbalance and exercise limitation in chronic heart failure patients. Whether metaboreflex is over-activated and participate to poor aerobic capacity in patients with hereditary transthyretin cardiac amyloidosis (CA-TTR) is unknown. Methods: Twenty-two CA-TTR patients (aged 76 ± 7, 68% male) with the V122I (p.Val142Ile) transthyretin underwent a thorough evaluation including heart rate variability metrics, electrochemical skin conductance (ESC), physical function cardiopulmonary exercise testing, and muscle metaboreflex assessment. Eleven control subjects were chosen for muscle metaboreflex assessment. Results: Age-matched controls (n = 11) and CA-TTR patients (n = 22) had similar metaboreflex sensitivity for heart rate, stroke volume, cardiac index and mean systemic arterial pressure. Compared with age-matched controls, metaboreflex sensitivity for systemic vascular resistance (−18.64% ± 6.91% vs 3.14% ± 23.35%) and minute-ventilation responses (−9.65% ± 14.83% vs 11.84% ± 23.1%) was markedly increased in CA-TTR patients. Values of ESC displayed positive correlations with stroke volume (r = 0.53, p = 0.011) and cardiac index (r = 0.51, p = 0.015) components of metaboreflex sensitivity, an inverse correlation with systemic vascular resistance (r = −0.55, p = 0.008) and a trend with mean arterial (r = −0.42, p = 0.052) components of metaboreflex sensitivity. Peak aerobic capacity (peak VO2%) displayed an inverse correlation with the ventilation component of metaboreflex sensitivity (r = −0.62, p = 0.015). Conclusion: Consistent with the “muscle hypothesis” in heart failure, it is proposed that deterioration of skeletal muscle function in hereditary CA-TTR patients may activate muscle metaboreflex, leading to an increase in ventilation and sensation of breathlessness, the perception of fatigue, and overall sympathetic activation.